The Preservation of in vivo Phosphorylated and Activated Uncoupling Protein 3 (UCP3) in Isolated Skeletal Muscle Mitochondria following Administration of 3,4-Methylenedioxymethamphetamine (MDMA aka Ecstasy) to Rats/Mice - Meegan, Mary; Porter, Richard (My University, 2012)
Previous researchers have demonstrated that 3,4-methylenedioxymethamphetamine (MDMA) induced hyperthermia, in skeletal muscle of animals, is uncoupling protein 3 (UCP3) dependent. In light of our investigations that in vivo phosphorylation of UCP1 is augmented under conditions of cold-acclimation, we set out to investigate whether (a) UCP3 was phosphorylated in vivo and (b) whether in vivo phosphorylation of UCP3 resulted in increased proton leak following MDMA administration to animals. Our data demonstrate that MDMA treatment (but not PBS treatment) of animals results in both in vivo serine and tyrosine phosphorylation of UCP3 in skeletal muscle mitochondria, isolated in the presence of phosphatase inhibitors to preserve in vivo phosphorylation. In addition, proton leak is only increased in skeletal muscle mitochondria isolated from MDMA treated animals (in the presence of phosphatase inhibitors) and the increased proton leak is due to phosphorylated UCP3. UCP3 abundance in skeletal muscle mitochondria is unaffected by MDMA administration. Preservation of UCP3 phosphorylation and increased proton leak is lost when skeletal muscle mitochondria are isolated in the absence of phosphatase inhibitors. We conclude that MDMA treatment of animals increases proton leak in skeletal muscle mitochondria by activating UCP3 through in vivo covalent modification of UCP3 by phosphorylation. Furthermore, we deduce that the MDMA induced hyperthermia in skeletal muscle is due to increased proton leak in vivo as a result of activation of UCP3 through phosphorylation.
PUBLISHED
Keywords: Biochemistry; Pharmacology; MDMA; Uncoupling protein; mitochondria; Immunology, Inflammation & Infection